Surface crystallographic structures of cellulose nanofiber films and overlayers of pentacene. (22nd January 2018) - Nakayama, Yasuo; Mori, Toshiaki; Tsuruta, Ryohei; Yamanaka, Soichiro; Yoshida, Koki; Imai, Kento; Koganezawa, Tomoyuki; Hosokai, Takuya
Abstract: Cellulose nanofibers or nanocellulose is a promising recently developed biomass and biodegradable material used for various applications. In order to utilize this material as a substrate in organic electronic devices, thorough understanding of the crystallographic structures of the surfaces of the nanocellulose composites and of their interfaces with organic semiconductor molecules is essential. In this work, surface crystallographic structures of nanocellulose films (NCFs) and overlayers of pentacene were investigated by two-dimensional grazing-incidence X-ray diffraction. The NCFs are found to crystallize on solid surfaces with the crystal lattice preserving the same structure of the known bulk phase, whereas distortion of interchain packing toward the surface normal direction is suggested. The pentacene overlayers on the NCFs are found to form the thin-film phase with an in-plane mean crystallite size of over 10 nm.